2010
DOI: 10.1093/hmg/ddq435
|View full text |Cite
|
Sign up to set email alerts
|

The β1 subunit of the Na,K-ATPase pump interacts with megalencephalic leucoencephalopathy with subcortical cysts protein 1 (MLC1) in brain astrocytes: new insights into MLC pathogenesis

Abstract: Megalencephalic leucoencephalopathy with subcortical cysts (MLC) is a rare congenital leucodystrophy caused by mutations in MLC1, a membrane protein of unknown function. MLC1 expression in astrocyte end-feet contacting blood vessels and meninges, along with brain swelling, fluid cysts and myelin vacuolation observed in MLC patients, suggests a possible role for MLC1 in the regulation of fluid and ion homeostasis and cellular volume changes. To identify MLC1 direct interactors and dissect the molecular pathways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 80 publications
4
67
0
Order By: Relevance
“…Altogether, these data confirm the hypothesis that MLC1 is involved in the regulation of organelle acidity, possibly by limiting vesicle acidification. A similar behavior has been described for the Na, K-ATPase which exerts an essential role in the maintenance of the slightly acidic pH typical of early endosomes in which it is localized (Cain and Murphy, 1988; Cain et al, 1989; Feldmann et al, 2007; Grabe and Oster, 2001) and whose direct interaction with MLC1 has been demonstrated by our group (Brignone et al, 2011). Future experiments will aim to clarify the exact mechanisms through which MLC1 can influence endosomal pH and the molecular and functional relationships between MLC1 and V-ATPase.…”
Section: Discussionsupporting
confidence: 82%
“…Altogether, these data confirm the hypothesis that MLC1 is involved in the regulation of organelle acidity, possibly by limiting vesicle acidification. A similar behavior has been described for the Na, K-ATPase which exerts an essential role in the maintenance of the slightly acidic pH typical of early endosomes in which it is localized (Cain and Murphy, 1988; Cain et al, 1989; Feldmann et al, 2007; Grabe and Oster, 2001) and whose direct interaction with MLC1 has been demonstrated by our group (Brignone et al, 2011). Future experiments will aim to clarify the exact mechanisms through which MLC1 can influence endosomal pH and the molecular and functional relationships between MLC1 and V-ATPase.…”
Section: Discussionsupporting
confidence: 82%
“…Expression of proteins allegedly associated or interacting with MLC113, 30, 31, 32, 33, 34 was evaluated by immunohistochemistry in 7‐month‐old mice. Compared to wild‐type animals, expression of the water channel aquaporin4 was redistributed along the cell bodies and processes of Glialcam ‐null astrocytes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Most previous studies on MLC1 function are based on patient leukocytes, artificial cell systems and scarcely available patient brain tissue obtained from biopsies and one autopsy 5, 6, 8, 9, 10, 15, 21, 30, 31, 32, 33, 34, 37. To allow research on MLC1 dysfunction in the intact brain, we previously developed an Mlc1 ‐null mouse that models the human disease 18.…”
Section: Discussionmentioning
confidence: 99%
“…K + homeostasis is tightly linked to the homeostasis of other ions, and MLC1 and GlialCAM colocalize and/or interact with several proteins involved in ion and water homeostasis. This includes the dystrophin glycoprotein complex,5, 45 Na + /K + ‐ATPase,46 the swelling‐sensitive cation channel, TRPV4,47 and the gap‐junction protein, connexin 43 20. MLC1 and GlialCAM may therefore play a central role in organizing these components necessary for astrocyte ion and water homeostasis.…”
Section: Discussionmentioning
confidence: 99%